Eufemisme dalam Visi dan Misi Ganjar-Mahfud tentang Lingkungan: Kajian Ekolinguistik Kritis - Tanuya Aini Harahap; Dwi Widayati; Rachmad Fadillah Maha (Universitas Sebelas Maret, 2024)
This research attempts to examine linguistic problems contained in environmental discourse in the speech of sources in the mass media in Indonesia, namely regarding euphemisms. This research is a qualitative descriptive study. Data was collected from online mass media, such as Kompas TV, Liputan6.com, and Jawa Pos using the listening method, with advanced techniques in the form of note-taking techniques. However, this data is limited to issues such as air pollution, the climate crisis and green economy programs on the environment. There are five types of euphemisms used by the resource person, Deddy, a spokesperson for the Ganjar-Mahfud National Winning Team (TPN) in the news on environmental discourse, namely loan word euphemisms, euphemisms where one word is replaced by another word, circumlocutionary euphemisms. , euphemistic forms of jargon (special terms), and euphemistic forms of abbreviations. This form is found in the form of words and phrases.